1996
DOI: 10.1182/blood.v87.4.1466.bloodjournal8741466
|View full text |Cite
|
Sign up to set email alerts
|

CD5-CD56+ T-cell receptor silent peripheral T-cell lymphomas are natural killer cell lymphomas [see comments]

Abstract: Non-Hodgkin's lymphomas are divided into B- and T-cell neoplasms. The existence and the clinical relevance of lymphomas derived from the third lymphocyte lineage, ie, natural killer (NK) cells are still controversial. NK cells are lymphocytes that mediate cytotoxicity without prior sensitization. NK cells also have phenotypic and genotypic characteristics: they express the NK-related antigen CD56, T- cell markers such as CD2 and CD7, but do not express CD5 and T-cell receptor (TCR) proteins, and their TCR locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(77 citation statements)
references
References 2 publications
4
72
1
Order By: Relevance
“…These results were in agreement with pathological and immunohistochemical findings (Sheridan et al, 1988;Emile et al, 1996;Jaffe, 1996). Although the morphology of tumour cells of NK-cell lymphomas is heterogenous, the tumour cells consistently express CD56, CD2, cytoplasmic CD3, but not surface CD3.…”
Section: Discussionsupporting
confidence: 90%
“…These results were in agreement with pathological and immunohistochemical findings (Sheridan et al, 1988;Emile et al, 1996;Jaffe, 1996). Although the morphology of tumour cells of NK-cell lymphomas is heterogenous, the tumour cells consistently express CD56, CD2, cytoplasmic CD3, but not surface CD3.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports have mentioned that few NK cell lymphoma cases included nodal involvement, 40,59 but our own showed nodal involvement in three of four patients. All cases with lymph node proliferation revealed a sinusoidal pattern of involvement.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, tumours were recognized in other extranodal sites, and the provisional term 'nasal-type' T/NK cell lymphoma was recommended. Recently, Emile et al 18 gave support to the concept that 'nasal and nasal-type T/NK cell lymphoma' is a distinct entity and provided further evidence for a derivation from NK cells, rather than from T cells. Macon et al 19 described six cases of lymphoma that they propose are derived from a unique subset of T cells, the NK-like or NK1þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jaffe et al 17 described rare cases that may present in the skin or soft tissue and relapse in the nose. In our review of the literature between 1983 and 1996, we found only 17 clear cases, 3,7,8,11,18,[21][22][23][24][25][26][27][28] of peripheral T-cell lymphoma with skin as well as nose metastasis. In six cases, 7,18,23,27,28 the lymphoma clearly proceeded from the skin.…”
Section: Discussionmentioning
confidence: 99%